A dyadic analysis of family adaptation among breast cancer patients and their spouses based on the framework of family stress coping theory - Zhangyi Ding; Yarong Fan; Gaoxiang Zhong; Xinmiao Zhang; Xichen Li; Yan Qiao; Huixia Cui (Frontiers in Public Health)
BackgroundThe active coping strategies of family members can help breast cancer patients better handle the crisis, and family adaptation is a manifestation of the family's active coping with the crisis. In the study of breast cancer, a disease that predominantly affects women, we explored the influence of spouses on patients' family adaptation. This aspect has not been explored in previous studies.PurposeIn recent years, with the development of family stress coping theory, cancer coping styles have shifted from an individual focus to a whole-family approach. This shift has the potential to help families of cancer patients adapt to the crisis. This study aimed to explore the correlation between dyadic coping, family adaptation, and benefit finding in couples with breast cancer.MethodsUsing convenience sampling, the study included 325 pairs consisting of breast cancer patients and their spouses who attended breast surgery, oncology, and chemotherapy sessions between April and November 2023. The survey utilized the General Information Questionnaire for patients and spouses, the Dyadic Coping Scale, the Benefit Finding Scale, and the Family Adaptability and Cohesion Evaluation Scales. Data analysis was conducted using SPSS 25.0 and Amos 24.0 software.ResultsIn the actor effect of dyadic coping on family adaptation, the benefit finding of patients and their spouses played a mediating role. Regarding the partner effect (B = 0.019, 95% CI = 0.003–0.045, P < 0.05), the dyadic coping of spouses indirectly affected the family adaptation of patients through the benefit findings of patients. The patient's dyadic coping can directly affect the spouse's family adaptation. The spouse's dyadic coping can influence the patient's benefit finding.ConclusionThere is a partial interaction between breast cancer patients and their spouses' dyadic coping, benefit finding, and family adaptation. Therefore, clinical staff should promptly identify patients and spouses with poor coping abilities and provide them with positive psychological interventions to enhance the dyadic coping abilities of both partners and assist them in overcoming the problems encountered during the treatment process, ultimately helping them better cope with family crises.